FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN EFEKTIVITAS TUTORIAL TATAP MUKA PROGRAM PENDIDIKAN DASAR DI UPBJJ-UT BANDA ACEH - Malta Malta (LPPM Universitas Terbuka, 2011)
Face-to-face tutorial is a type of student services provided by Universitas Terbuka at each regional center. Factors which influence the effectiveness of face-to-face tutorial at Banda Aceh regional center were discussed. The research method was descriptive-corelational. There were 66 tutors as respondents filled the questionnaire. Data collection was carried out from April until June 2010. In analyzing the data, correlation test of Rank Spearman was used. The results showed that (1) the effectiveness of face-to-face tutorial was at medium level; (2) factors which influence the effectiveness of face-to-face tutorial were the infrastructure, the contribution of regional center and the quantity of face-to-face tutorial